The Lower Siwalik - Basement unconformity in the Sub-Himalaya of eastern Nepal and its significance - Shrestha, R. B.; Sharma, S. R. (Journal of Nepal Geological Society, 1996)
South of the Main Boundary Thrust (MBT), in the Sub-Himalaya of central and eastern Nepal, pre Siwalik rocks in the form of fault bound slices are known to occur. Recently the present authors have mapped these rocks in the Udayapur district of south eastern Nepal. In the area about 1 km wide pre Siwalik rocks extend for over 50 km along a NE-SW direction. In the eastern area around Ttntale village (near the Tawa Khola-Baijanatb Khola confluence), the stromatolitic dolomites of Tintale Formation of the pre-Siwalik Group is overlain by the Lower Siwalik with a prominent unconformity marked by a 4.5 m thick basal conglomerate. Likewise, in the western area along the Manba Khola, the Siwalik Group overlies the pink sandstones and shales of the Manba Formation of the pre-Siwalik Group with an unconformity, again with a conglomerate horizon at the base. It is perhaps the only occurrence where the base of the Siwalik Group is recorded in Nepal. In this part of the Himalaya, the Siwalik sediments directly overlie the Precambrian-Lower Paleozoic (?) basement rocks with an unconformity. The basement rocks along with its Siwalik cover was brought to the surface by thrusting within the Sub-Himalaya.